Compared interest between hair analysis and urinalysis in doping controls. Results for amphetamines, corticosteroids and anabolic steroids in racing cyclists - Gaillard, Y.; Vayssette, F.; Pepin, G. (Forensic Science International, 2000)
In France during a famous bicycle race, the newspapers documented the degree in which doping seemed to be supervised in some teams by managers and doctors. Use of anabolic steroids and other substances was officially banned in the mid-seventies by sports authorities. This policy has been enforced through urine testing before competition. It is well known, however, that a latency period is all that is necessary to defeat these tests. Nevertheless, hair analysis could be a promising tool when testing for periods that are not accessible to urinalysis any more. We have developed different sensitive methods for testing hair for amphetamines, anabolic steroids and their esters and corticosteroids. For amphetamines, 50 mg of hair were digested with 1 M NaOH, extracted with ethyl acetate, derivatized with TFA and analyzed by gas chromatography positive chemical-ionization mass spectrometry. For corticosteroids, 50 mg of powdered hair were treated with methanol in an ultrasonic bath and subsequently purified using a C18 solid phase extraction column. Analysis was realized by high performance liquid chromatography coupled to electrospray-ionization tandem mass spectrometry. For anabolic steroids and their esters, 100 mg of powdered hair were treated with methanol in an ultrasonic bath for extraction of esters, then alkaline digested with 1 M NaOH for an optimum recovery of other drugs. The two liquid preparations were subsequently extracted with ethyl acetate, pooled, then finally highly purified using a twin solid phase extraction on aminopropyl and silica cartridges. Residue was derivatized with MSTFA prior to injection. Analysis was conducted by gas chromatography coupled to a triple quadrupole mass spectrometer. Thirty cyclists were sampled and tested both in hair and in urine. Amphetamine was detected 10 times in hair (out of 19 analyses) compared to 6 times in urine (out of 30 analyses). Corticosteroids were detected 5 times in hair (methylprednisolone 1 case, triamcinolone acetonide 3 cases and hydrocortisone acetate 1 case) in hair (out of 12 analyses) compared to 12 times (triamcinolone acetonide 10 cases and betamethasone 2 cases) in urine (out of 30 analyses). Anabolic steroids were detected twice (nandrolone 1 case, and testosterone undecanoate 1 case) in hair (out of 25 analyses) compared to none in urine (out of 30 analyses).